PERAN PERSATUAN WARTAWAN INDONESIA DALAM PENCEGAHAN TINDAK PIDANA TERHADAP WARTAWAN STUDI KASUS DI WILAYAH DKI JAKARTA - Marpaung, Mitasari Febyanti; Marlina, Marlina; Desiandri, Yati Sharfina (Smart Education, 2026)
Abstract: The high number of cases of violence, criminalization, and impunity demonstrates the weak legal protection for journalists. On the other hand, the emergence of unprofessional journalists and media has exacerbated the situation by triggering professional abuse and legal conflicts. The Indonesian Journalists Association (PWI) strives to provide protection through legal assistance, mediation with the Press Council, and ethical guidance, but structural and regulatory challenges have made the effectiveness of protection less than optimal. This condition emphasizes the need for regulatory harmonization, strengthening the role of PWI, and increasing the understanding of officials so that press freedom and journalist security are truly guaranteed. The research method used is normative legal research supported by empirical data. The normative-empirical legal research method examines how people apply normative legal rules (statutes) in their actions in each specific legal event in a society. Legal protection for journalists in DKI Jakarta already has a strong basis through the Press Law, but has not been implemented effectively due to overlaps with the Criminal Code and the ITE Law which trigger the criminalization of journalists. The Indonesian Journalists Association (PWI)'s efforts through advocacy, code of ethics dissemination, and cross-sector collaboration have helped improve protection, but their reach remains limited. Internal barriers within the organization and a lack of understanding among law enforcement officials regarding the application of the Press Law as lex specialis are key factors weakening its effectiveness. Therefore, regulatory harmonization and increased commitment by law enforcement officials are needed to ensure journalists receive legal certainty when carrying out their duties. Keywords: PWI (Indonesian Journalists Association), Journalist Protection, Press Criminalization Abstrak: Tingginya kasus kekerasan, kriminalisasi, dan impunitas memperlihatkan lemahnya perlindungan hukum bagi wartawan. Di sisi lain, munculnya oknum wartawan dan media tidak profesional turut memperburuk situasi karena memicu penyalahgunaan profesi dan konflik hukum. PWI berupaya memberikan perlindungan melalui pendampingan hukum, mediasi dengan Dewan Pers, dan pembinaan etik, namun tantangan struktural dan regulatif membuat efektivitas perlindungan belum optimal. Kondisi ini menegaskan perlunya harmonisasi regulasi, penguatan peran PWI, serta peningkatan pemahaman aparat agar kebebasan pers dan keamanan wartawan benar-benar terjamin. metode penelitian yang digunakan adalah penelitian hukum normatif yang didukung data empiris. Metode penelitian hukum normatif-empiris yang melihat bagaimana orang menerapkan aturan-aturan hukum normatif (undang-undang) dalam aksinya pada setiap peristiwa hukum tertentu dalam suatu masyarakat Perlindungan hukum bagi wartawan di DKI Jakarta sudah memiliki dasar yang kuat melalui UU Pers, tetapi belum berjalan efektif karena tumpang tindih dengan KUHP dan UU ITE yang memicu kriminalisasi wartawan. Upaya PWI melalui advokasi, sosialisasi kode etik, dan kerja sama lintas sektor sudah membantu meningkatkan perlindungan, namun jangkauannya masih terbatas. Hambatan internal dalam organisasi serta rendahnya pemahaman aparat penegak hukum mengenai penerapan UU Pers sebagai lex specialis menjadi faktor utama yang melemahkan efektivitas perlindungan. Karena itu, diperlukan harmonisasi regulasi dan peningkatan komitmen aparat agar wartawan memperoleh kepastian hukum saat menjalankan tugasnya. Kata kunci: PWI (Persatuan Wartawan Indonesia), Perlindungan Wartawan, Kriminalisasi Pers